Características de maquinado de 32 especies de madera - Martínez Castillo, José L.; Martínez-Pinillos Cueto, Enrique (Instituto de Ecología, A.C., 2016)
The use of potentially commercial lesser-known woods, quite  often is limited because of the lack of knowledge on their machining characteristics. Tests were conducted for three processes commonly used in wood machining (boring, shaping and mortising), on 32 species from tropical and temperate forests, based on the ASTM D-1666 standard. Tests were carried out with wood conditioned at 8% moisture content. Machined surface  characteristics were evaluated, grouping the wood species according to the surface quality.